2019
DOI: 10.14201/fjc201919205222
|View full text |Cite
|
Sign up to set email alerts
|

La publicidad televisiva dirigida a menores en España: seguimiento del código PAOS

Abstract: En un contexto de preocupación por la fuerte prevalencia de la obesidad entre los niños españoles, el debate sobre la publicidad televisiva de alimentos para niños alcanza gran importancia. Aunque existen otros factores que influyen sobre la obesidad infantil, hay evidencias de que los mensajes publicitarios tienen un gran impacto sobre los hábitos alimenticios de los niños. Mediante un análisis de contenido, el objetivo de esta investigación es analizar y evaluar la eficacia del Código PAOS en 2018 como instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In accordance with other studies [52,53,64,65], it was found that among the most used strategies to advertise food are promotions or offers, the appearance of known characters, or giving them away as gifts, clearly violating some of the standards that appear expressly in the norm. According to what was observed, these advertising strategies could be classified as misleading or abusive since the food advertised is linked with properties that are actually difficult to find.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In accordance with other studies [52,53,64,65], it was found that among the most used strategies to advertise food are promotions or offers, the appearance of known characters, or giving them away as gifts, clearly violating some of the standards that appear expressly in the norm. According to what was observed, these advertising strategies could be classified as misleading or abusive since the food advertised is linked with properties that are actually difficult to find.…”
Section: Discussionsupporting
confidence: 87%
“…There is a certain predisposition prior to the adhesion and linkage to the PAOS Code by the companies. However, this predisposition does not correspond with the purpose pursued by the administrations and the real achievement of the objectives, since it is clear that self-regulation is not an effective mechanism to avoid or reduce the exposure of children to advertising of unhealthy foods and beverages and, therefore, to promote a healthy lifestyle from childhood, as previous studies have evidenced [21,28,30,31,52,64] referring to other media, such as television. In this case, we study specifically mobile devices, because these previous studies did not look at other media different from television, and we are starting from the same base.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations